Fiber optic multipoint remote methane sensing system based on pseudo differential detection. (March 2019) - Wang, Zhongmin; Chang, Tianying; Zeng, Xiangbao; Wang, Haixu; Cheng, Liyao; Wu, Chongjian; Chen, Jiandong; Luo, Zhengchun; Cui, Hong-Liang
Abstract : An all optical fiber multipoint methane sensing system based on a new pseudo differential detection technique is developed for continuous remote monitoring of methane gas concentration, and is presented in this paper. To the best of the authors' knowledge, the pseudo differential detection technique employing high frequency square modulation is for the first time applied to gas sensing here. In this new scheme, light intensity fluctuations induced by the laser's long-term instability, variation of environmental temperature, and vibration of the optical cable, etc., are eliminated. The effectiveness of the new approach is analyzed theoretically and demonstrated experimentally. Test results show that the performance of the proposed simpler sensing system realizing multipoint remote detection is comparable with system using second harmonic detection technique. Abstract: An all optical fiber multipoint methane sensing system based on a new pseudo differential detection technique, operating at the near-infrared wavelength of 1645.54 nm, is developed for continuous remote monitoring of methane gas concentration. A pseudo differential detection technique employing high frequency square modulation is applied to tunable diode laser absorption spectroscopy (TDLAS), and methane concentration is derived from the variation of square-wave amplitude. The efficacy of the new approach is analyzed theoretically and demonstrated experimentally. Test results show that the performance of the proposed simpler sensing system realizing multipoint remote detection is comparable with systems employing the second harmonic detection technique. The developed sensing system was deployed in a working underground utility tunnel in the Hengqin special district (Zhuhai, China) in April 2017, and has been functioning satisfactorily since.